Middle Triassic deeper-marine volcano-sedimentary successions in western Slovenia - Dragomir Skaberne; Jože Čar; Maja Pristavec; Boštjan Rožič; Luka Gale (Geologija)
A Ladinian – Carnian volcano-sedimentary succession from western Slovenia, paleogeographically belonging to the western Slovenian Basin, is presented in 17 sections. Except for the lowermost part, which is dominated by volcanics and volcaniclastics, most of the succession is dominated by shale, sandstone, and micritic limestone. Various authors use the name Pseudozilja and/or Amphiclina formation for this part, which is dominated by clastics, but they disagree on the differences between the formations. The lower Pseudozilja formation, represented by the Malenski Vrh section, comprises diabase, tuf and shale. No substantial differences in lithological composition have been observed between the upper Pseudoziljaformation and the Amphiclina formation, which are predominantly composed of shale, sandstone, and limestone. The shale and sandstone are largely composed of quartz, feldspar, and lithic grains (especially volcanics), which vary in proportions. Limestone varieties comprise hemipelagic limestones and resedimented carbonates deposited by gravity-flows. Deposition of the Ladinian – Carnian volcano-sedimentary succession took place on or near the continental slope that was generally inclined to the S, with the direction of transport mainly from N to S.